FAKTOR-FAKTOR KESULITAN BELAJAR DALAM MENGIKUTI MATA PELAJARAN KETERAMPILAN TATA BUSANA SISWA SMPN 1 SURUH SEMARANG - Indriati Purnami; Yasmi Teni Susiati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The objective of the research is to know the factors causing learning difficulties for Tata Busana skill faced by the eighth grade students in understanding Tata Busana skill subject. The type of the research is descriptive. Samples are taken using proportional random sampling technique. Data are collected by questionnaire and documentation.Instruments are tested their validity and reliability. Data analysis technique applies descriptive analysis technique. The results show that variable of learning difficult factor in understanding the Tata Busana Skill subject is high category ( relative frequency 44,87%). It means that learning difficulty is a serious problem faced by all students because there is a disturb, either coming from internal or external factor to get a good result as learning interest, availability of learning tools, and teacher’s competition for teaching, but it does not happen in learning tata busana skill subject because it is high enough.